Report of the Commission on Narcotic Drugs on the Fifty-Ninth Session (11 December 2015 and 14-22 March 2016) - United Nations Department for General Assembly; Conference Management (United Nations, 2017)
This is the official record of the report of the Commission on Narcotic Drugs on its fifty-ninth session 11 December 2015 and 14-22 March 2016.